Infrared and Terahertz Compatible Absorber Based on Multilayer Film - Yang, Mingyang; Zhou, Ming; Yu, Jianwen; Zhang, Yibo; Xu, Benyan; Cheng, Wenjun; Li, Xuyin (Frontiers in Physics, 2021)
In this paper, a similar Fabry-Perot cavity structure utilizing multilayer film structure consist of an ultrathin metal film is demonstrated for absorbing the infrared ray. This structure has low emissivity in the atmospheric window (3-5 and 8-14 μm) and high emissivity in the non-atmospheric window (5-8 μm). These properties improved the stealth performance cause the high emissivity in 5-8 μm can radiate more energy to reduce its temperature. Based on this, the periodic microstructures were added to the surface of the materials that enhanced the absorption of terahertz wave (0.1-2.7 THz). The absorber based on multilayer film has simple structure and low manufacturing cost. This work may provide a new strategy for infrared and terahertz compatible stealth technology.